1969
DOI: 10.1149/1.2411523
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of the State of the Art and Some Recent Results on Electromigration in Integrated Circuit Aluminum Metallization

Abstract: This paper presents a report of the state of the art with respect to the electromigration phenomenon in integrated circuit (IC) metallization. Reported here are some of the latest research efforts, including the authors' research, on the effects of dielectric overcoatings on electromigration in aluminum interconnections. This research has shown that dielectric overcoating of the aluminum stripes yields interconnections with greater mean time between failures than found in many conventional integrated circuits.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, it was revealed that SPS causes fragmentation of the gold thin foil on the cathode. The fragmentation of thin foils and intrusion into the cathode can be well explained by electromigration, which is often reported for narrow wires in large-scale integration (LSI)[39]. The electron flux on the large current density (~500 A cm −2 ) scatters atoms on their conduction path with their huge momentum, which leads fragmentation and intrusion of the foils.…”
mentioning
confidence: 96%
“…Therefore, it was revealed that SPS causes fragmentation of the gold thin foil on the cathode. The fragmentation of thin foils and intrusion into the cathode can be well explained by electromigration, which is often reported for narrow wires in large-scale integration (LSI)[39]. The electron flux on the large current density (~500 A cm −2 ) scatters atoms on their conduction path with their huge momentum, which leads fragmentation and intrusion of the foils.…”
mentioning
confidence: 96%
“…The values of Ea found are listed in Table ItI. Many values of Ea were obtained by lifetesting (142, 144, [164][165][166][167][168]. Measurement of transported volumes (141, [169][170][171][172] and resistance changes (173,174) were also used and resultant Ea values are included.…”
Section: Contact Stability--postmetallization Processing Suchmentioning
confidence: 99%